Removal of retrievable inferior vena cava filters before discharge: Is it associated with increased incidence of pulmonary embolism?. Issue 5 (November 2019) - Robbins, Justin M.; Garwe, Tabitha; McCarthy, Cullen K.; Sarwar, Zoona; Gonzalez, Robert A.; Zander, Tyler L.; Jalla, Aditi N.; Conner, Keri S.; Stewart, Kenneth E.; Albrecht, Roxie M.
Abstract : BACKGROUND: Severely injured trauma patients are at high risk of developing deep venous thrombosis and pulmonary emboli (PE), and may have contraindications to prophylactic or therapeutic anticoagulation. Retrievable inferior vena cava filters (rIVCFs) are used to act as a mechanical obstruction to prevent PE in high risk populations and those with deep venous thrombosis who cannot be anticoagulated. The removal rate of rIVCFs is variable in trauma centers, including our previous published rate of 50% to 89%/year. Indwelling filters carry a risk of significant morbidity and the success of retrieval decreases as the dwell time increases. We hypothesized that once patients could receive appropriate prophylactic or therapeutic anticoagulation, rIVCF could be removed before hospital discharge without impact on occurrence or recurrence of PE. METHODS: All trauma patients with rIVCF placed and removed between January 2006 and August 2018 were reviewed. We collected data from record review from admission to 6 months postfilter removal, including demographics, filter indication, filter type, dwell time, placement and removal complications, antithrombosis medications, location of venous thromboembolism, complications, and discharge disposition. Exposure of interest was timing of filter removal: before (BEF) or after hospital discharge (AFT). The outcome of interest was whether the patient had a documented PE within 6 months of filter removal. RESULTS: A total of 281 rIVCFs were placed, 218 were eligible for removal, 72.4% (158/218) were retrieved with 63% (100/158) removed before discharge. Mean filter duration was 26 days and 103 days for the before and after groups, respectively. No differences ( p > 0.05) were noted in the distribution of demographic and clinical factors except for filter indication (venous thromboembolism indication, 95% in AFT vs. 74% in BEF, p = 0.0043). Postremoval PE rates were 0% BEF and 1% AFT (Fisher's exact test, p = 1.000). CONCLUSION: Our results suggest that removal of rIVCFs before discharge once patients are appropriately anticoagulated is a safe strategy to improve retrieval rates. LEVEL OF EVIDENCE: Therapeutic, level V.